2007
DOI: 10.1152/ajpendo.00462.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational inheritance of the insulin-resistant phenotype in embryo-transferred intrauterine growth-restricted adult female rat offspring

Abstract: To determine mechanisms underlying the transgenerational presence of metabolic perturbations in the intrauterine growth-restricted secondgeneration adult females (F2 IUGR) despite normalizing the in utero metabolic environment, we examined in vivo glucose kinetics and in vitro skeletal muscle postinsulin receptor signaling after embryo transfer of first generation (F1 IUGR) to control maternal environment. Female F2 rats, procreated by F1 pre-and postnatally nutrientand growth-restricted (IUGR) mothers but emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 37 publications
3
80
0
2
Order By: Relevance
“…In contrast, studies by Gill-Randall et al (18) have shown that embryos from the diabetic Goto-Kakizaki rat developing in the normoglycemic Wistar intrauterine environment developed diabetes, showing that genetic predisposition to diabetes is not alleviated by a euglycemic intrauterine environment. In another study, embryos from intrauterine growth-retarded F1 generation females, when transferred to a normal intrauterine environment, still developed the maternal phenotype, indicating the dominant effect of epigenetic modifications (36). Future studies should determine whether in the third generation of HC rats genetic propensity (established probably due to epigenetic alterations) would gain dominance over the intrauterine environment by transferring embryos from 2-HC rats to MF females.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, studies by Gill-Randall et al (18) have shown that embryos from the diabetic Goto-Kakizaki rat developing in the normoglycemic Wistar intrauterine environment developed diabetes, showing that genetic predisposition to diabetes is not alleviated by a euglycemic intrauterine environment. In another study, embryos from intrauterine growth-retarded F1 generation females, when transferred to a normal intrauterine environment, still developed the maternal phenotype, indicating the dominant effect of epigenetic modifications (36). Future studies should determine whether in the third generation of HC rats genetic propensity (established probably due to epigenetic alterations) would gain dominance over the intrauterine environment by transferring embryos from 2-HC rats to MF females.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a study focusing on the F2 generation uncovered that rats with low maternal birth weight due to late-gestation (e19) uteroplacental insufficiency exhibited a sex-specific reduced insulin response and altered pancreatic morphology (55). In another study, female F2 rats exhibited increased hepatic weight with aberrant glucose and insulin metabolism (74). Natural experiments and comparisons to human populations have borne out the validity of the rodent IUGR models, finding similarities in epigenetic metabolic regulation (23,33,55,65).…”
Section: Discussionmentioning
confidence: 99%
“…A higher susceptibility of the female progeny to epigenetic insults has been already recognized in animals (20,21). To explain this sexual dimorphism, it has been hypothesized that the differential susceptibility to complex diseases, such as obesity and diabetes, in men and women is mediated by differences in the epigenetic regulation of genes induced by sex hormones (22).…”
Section: ϫ2mentioning
confidence: 99%